Organic functional group preparations. - Sandler, Stanley R., 1935- (Organic chemistry, 1972)
Organic Functional Group Preparations, Volume III describes 13 organic functional groups and presents a critical review of their available methods of synthesis with preparative examples of each. The book puts special attention to the presentation of specific laboratory directions for the many name reactions used in describing the synthesis of these functional groups. Each chapter deals with the preparation of a given functional group by various reaction types (condensation, elimination, oxidation, reduction) and a variety of starting materials. Acetals and ketals, anhydrides, and thiohydroxami.